Genome-wide analysis of soybean cinnamyl alcohol dehydrogenase genes identifies GmCAD3 as a positive regulator of Fusarium oxysporum resistance - Zhou, Runnan; You, Jia; Li, Jinrong; Li, Han; Lamlom, Sobhi F.; Ren, Honglei; Wang, Jiajun (Frontiers in Plant Science, 2025)
BackgroundCinnamyl alcohol dehydrogenase (CAD) catalyzes the final step in monolignol biosynthesis and plays critical roles in lignin-mediated plant defense against pathogens. Despite soybean global agricultural importance, systematic characterization of the CAD gene family and its role in disease resistance remains lacking.MethodsWe performed comprehensive genome-wide identification, phylogenetic analysis, and expression profiling of soybean CAD genes. Haplotype diversity was assessed through whole-genome resequencing of 289 Chinese soybean accessions. Population genetic parameters (Fst, π, Tajima’s D) were calculated to examine selection signatures. Functional validation was conducted through promoter activity assays, subcellular localization, and transgenic hairy root overexpression challenged with Fusarium oxysporum.ResultsSeven GmCAD genes with conserved catalytic domains (PF00107, PF08240) were identified and grouped into four phylogenetic clusters. Expression profiling revealed strong pathogen-induced upregulation, with GmCAD3 showing the most dramatic response (8.64-fold induction at 14 days post-inoculation). Three major GmCAD3 haplotypes were identified based on seven SNPs (five promoter, two coding sequence). Haplotype 2 exhibited significantly enhanced disease resistance (disease severity index 72.4 ± 2.1) compared to Haplotype 1 (88.6 ± 1.8; P < 0.001), correlating with superior promoter activity. Population genetic analysis indicated maintenance of multiple functional haplotypes during domestication. Transgenic validation confirmed that GmCAD3 overexpression increases CAD enzyme activity (2–3 fold), lignin accumulation (70-88%), and pathogen resistance.ConclusionsThis study provides the first comprehensive characterization of the soybean CAD gene family and demonstrates that GmCAD3 functions as a key regulator of lignin-mediated defense against F. oxysporum. Natural haplotype variation in GmCAD3 provides valuable molecular markers for breeding Fusarium-resistant soybean cultivars.